The political implications of kant's theory of knowledge rethinking progress - Lahat, Golan Moshe; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Based on an insightful and innovative reading of Kant's theory of knowledge, this book explores the political implications of Kant's philosophical writings on knowledge. It suggests that Kant offers a stable foundation for the reconsideration of the idea of progress as crucial in matters of political management at the outset of the 21st Century.
Keywords: Science; Science; Science, general